2012
DOI: 10.1007/bf03262489
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Evaluation of an Inpatient Consumer Survey Measuring Satisfaction with Psychiatric Care

Abstract: The overall findings from this study provide evidence that the ICS is a reliable measure of consumer satisfaction in psychiatric inpatient settings. The analysis has shown the ICS to provide valid and reliable results and to focus on the specific concerns of consumers of psychiatric inpatient care. Scores by item indicate that opportunity for improvement exists across healthcare organizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…All but three studies [ 31 , 33 , 36 ] reported internal consistency and could be rated using COSMIN box A. Ratings for internal consistency were either poor [ 13 , 17 , 18 , 28 , 30 , 34 , 35 , 37 , 41 , 44 , 45 ] or fair [ 16 , 29 , 32 , 38 40 , 42 , 43 , 46 53 ]. Reliability (box B) was only assessed in six studies, either resulting in poor [ 32 , 37 , 39 ] or fair ratings [ 18 , 36 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All but three studies [ 31 , 33 , 36 ] reported internal consistency and could be rated using COSMIN box A. Ratings for internal consistency were either poor [ 13 , 17 , 18 , 28 , 30 , 34 , 35 , 37 , 41 , 44 , 45 ] or fair [ 16 , 29 , 32 , 38 40 , 42 , 43 , 46 53 ]. Reliability (box B) was only assessed in six studies, either resulting in poor [ 32 , 37 , 39 ] or fair ratings [ 18 , 36 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Reliability (box B) was only assessed in six studies, either resulting in poor [ 32 , 37 , 39 ] or fair ratings [ 18 , 36 , 43 ]. Measurement error was not reported in any study and could therefore not be rated with COSMIN box C. Content validity (box D) was assessed by most studies with a high variability of scores, ranging from several studies rated as poor [ 13 , 16 , 28 , 35 , 37 , 38 , 45 47 , 49 52 ] to one single study rated as excellent [ 34 ]. Structural validity (box E) was also assessed by most studies with only the study on the Genetic Counseling Outcome Scale [ 18 ] being rated as good and all other studies receiving poor [ 28 , 30 , 31 , 34 , 36 , 37 , 41 ] or fair ratings [ 16 , 17 , 29 , 32 , 35 , 38 40 , 42 – 44 , 46 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations